Sex Differences in Clinical Characteristics and Prognosis in Primary Thrombotic Antiphospholipid Syndrome - Huang, Yongfa; Liu, Huazhen; Qi, Wanting; Du, Le; Li, Mengtao; Zeng, Xiaofeng; Guo, Xiaoxiao; Zhao, Jiuliang; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2022)
Objectives This study aims to investigate whether there are sex differences in clinical characteristics and prognosis in patients with primary thrombotic antiphospholipid syndrome (ptAPS). Methods Between January 2013 to July 2021, 154 consecutive patients diagnosed with ptAPS were prospectively recruited. Multivariable Cox regression was used to evaluate the association between gender and the composite endpoint including thromboembolic recurrence or all-cause death during follow-up. Results Totally 80 (52%) male and 74 (48%) female ptAPS patients were included, and male ones had a higher percentage of smokers/ex-smokers (50 [62%] vs 6 [8%], P < 0.001) and hyperhomocysteinemia (26 [32%] vs 9 [12%], P = 0.003). The baseline thromboembolic events were similar in two genders, except for limb ischemia (15 [19%] in male vs 1 [1%] in female, P < 0.001). During a median follow-up of 42 months, the composite endpoint occurred in 30 (38%) male and 15 (20%) female patients (P = 0.019). Male gender (HR 2.499, 95% CI [1.316, 4.743], P = 0.005) and warfarin administration (HR 0.482, 95% CI [0.257, 0.905], P = 0.023) remained independent prognostic factors for the composite endpoint. Male gender (HR 3.699, 95%CI [1.699, 8.246], P = 0.001) and isolated lupus anticoagulant positivity (HR 2.236, 95%CI [1.039, 4.811], P = 0.040) were independent predictors for thromboembolic recurrence. Conclusion There are sex disparities in the clinical characteristics in patients with ptAPS and male gender is an independent predictor for the poor prognosis. Male patients with isolated lupus anticoagulant positivity have the highest risk of thromboembolic recurrence.